Predisposing factors and impact of healthcare-associated infections in patients with status epilepticus - Dannys RIVERO RODRÍGUEZ; Claudio SCHERLE MATAMOROS; Daniela DICAPUA SACOTO; Sara GARCIA-PTACEK; Yanelis PERNAS SANCHEZ; Graham PLUCK (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Few studies have evaluated the incidence, predisposing factors and impact of healthcare-associated infections (HCAIs) in relation to outcomes among patients with status epilepticus (SE). Objective: To investigate the variables associated with development of HCAIs among patients with SE and the impact of factors relating to HCAIs on mortality at three months. Methods: This study was a retrospective analysis on our prospectively collected dataset, from November 2015 to January 2019. The sample included all consecutive patients diagnosed with SE who were treated at Hospital Eugenio Espejo during that period. In total, 74 patients were included. Clinical variables such as age, etiology of SE, Charlson comorbidity index (CCI), hospital length of stay, refractory SE (RSE) and outcomes were analyzed. Results: HCAIs were diagnosed in 38 patients (51.4%), with a preponderance of respiratory tract infection (19; 25.7%). Prolonged hospital length of stay (OR=1.09; 95%CI 1.03-1.15) and CCI≥2 (OR=5.50; 95%CI 1.37-22.10) were shown to be independent variables relating to HCAIs. HCAIs were associated with an increased risk of mortality at three months, according to Cox regression analysis (OR=2.23; 95%CI 1.08-4.58), and with infection caused by Gram-negative microorganisms (OR=3.17; 95%CI 1.20-8.39). Kaplan-Meier curve analysis demonstrated that HCAIs had a negative impact on the survival rate at three months (log rank=0.025). Conclusions: HCAIs are a common complication among Ecuadorian patients with SE and were related to a lower survival rate at three months. Prolonged hospital length of stay, RSE and CCI≥2 were associated with the risk of developing HCAIs.